ÙØ¸ÙÙÙØ© Ø§ÙÙØºÙØ© ÙÙ Ø§ÙØ¹ÙÙÙÙØ© Ø§ÙÙÙÙØ§ØµÙÙÙØ© - Ridha, Rasyid (Hunafa: Jurnal Studia Islamika, 2007)
This article deals with the functions of a language in a communication act. People communicate using a language to convey their points to others. A communication act contains 1) a locutionary act; 2) an illocutionary act; and 3) a perlocutionary. Therefore, to reflect the above three communication acts, people have to know, first, the communicative functions of a language in order to know how to communicate with others effectively, both in articulating voices, words, and sentences. Besides, a message they convey can be quickly deconstructed and interpreted by listeners.Kata Kunci:Â Â Â  Â ÙÙØªÙØ§Ø Ø§ÙÙÙÙÙ, Fungsi Komunikatif Bahasa Â